Satellitenbildkarte/Satellite Image Map 1:1 000 000 Ritscherhochland SS 28-30, Antarktis - Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie); Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1993)
Satellite image map, Topographic map SS 28-30 Ritscherhochland; Satellite imagery recorded between 18 Feb 1973 and 23 Nov 1975; Satellite image mosaicking, Geocoding and Satellite image map compilation, see: Sievers, J., et al. (1989); Inset maps: Location diagram, Index to adjoining sheets at 1:1 000 000 scale, Geographical names diagram, Listing of Landsat-MSS recording data and Satellite imagery coverage diagram displaying also the positions of identifiable ground control; Sources used for: Satellite imagery, Topographic information, Spot heights, Ground control, Positional accuracy, Geographical Norwegian, German and English Place-names, Generic terms: see map legend; Series of 10 published maps at 1:1 000 000 scale based on the IMW map sheet numbering system: Ekströmisen SR 29-30, Lassiter Coast SS 19-21, Brunt Ice Shelf SS 25-27, Ritscherhochland SS 28-30, Ronne Ice Shelf ST 17-20, Berkner Island ST 21-24, Coats Land ST 25-28, Institute Ice Stream SU 16-20, Filchnerschelfeis SU 21-25, Shackleton Range SU 26-30; Scale: 1:1000000; Projection: Lambert Conformal Conic; Bounding Box: POLYGON ((-18 -72, 0 -72, 0 -76, -18 -76, -18 -72)); Datum: WGS72